Fiber Bragg grating based displacement sensors with low visual impact for structural health monitoring applications: Monastery of Batalha case - Pereira, Luís (2024)
The preservation of heritage structures and buildings is a major concern to guarantee access of the cultural and architectural values to current and future generations. It also contributes significantly to the society in terms of identity, economy, education, and tourism. Due to their ancient nature, combined with the human activity (in and/or around these structures) and the environmental conditions, these structures are particularly susceptible to material deterioration and damage, that can compromise their integrity and the human safety. Therefore, it is crucial the implementation of an adequate monitoring system to analyse the static and dynamic responses of structures. In this paper, we discuss the development and installation of a sensing system for long-term monitoring of crack and joint movements, comprising eight displacement sensing devices and two temperature sensors, in the Monastery of Batalha, Portugal. The displacement sensing devices are formed by transparent small dimension holders and fiber Bragg gratings, with minimal intrusion and very low visual impact. They are relatively easy to fabricate, reproduce, and install, being a viable, efficient, and cost-effective alternative for Structural Health Monitoring sensing applications. Furthermore, they present simple design and principle of operation, which contributes to a straightforward installation and operation, and great versatility, as the alternative pre-strain mechanism of these devices allows to easily adjust the distance between the optical fiber holders. The operational performance of the sensing devices was analysed, and the monitoring results obtained during the following months after their installation are presented and discussed. The long-term data gathered by this sensing system can in the future be used to evaluate possible interventions.